Digital Acculturation: A Study - H, Aiswarya; M S, Sree Lekshmi; Chandran, Shilpa M; Aich, Shibani Chakraverty (International Journal of Psychosocial Rehabilitation, 2020)
Digital media is an exceptional tool for expression, entertainment, enlightenment and empowerment. It is an influential platform which has an undeniable reach across the world penetrating different cultures, races, and ethnicities. On the other hand, culture is an integral part of human civilization that is under constant flux based on the different exposures it receives. Therefore, digital media’s influence on culture is phenomenal due to its far reach and effectiveness that impacts the masses globally. This paper attempts to analyse the synergistic relation between digital media and culture on the basis of its merits and demerits. The study is carried out by scrutinising the influences of a foreign culture on native culture through the medium of digital platforms, digital media’s influence on culture and vice versa.